Layanan Informasi Publik Dan Pengaduan Masyarakat Pemerintah Kota Kupang - Yohanes Payong (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2020)
The need for public information is increasing in developing personalities in the social environment. Information services and public complaints are a basic right for citizens in accordance with the mandate of Law Number 14 of 2008 concerning Public Information Openness, where there are several types of information, including: information that must be provided and announced periodically, immediately, and which available at any time. The Regional Apparatus Organization (OPD) within the Kupang City Government has not fully implemented the mandate of the law as mentioned above. Based on the section that handles public information at the Regional Apparatus Organization in the City Government of Kupang, 35% (OPD) stated that there is already public information, but it is still limited to one particular section, not specifically in one unit. Meanwhile, 32% (OPD) of the units assigned to handle public complaints had units/divisions but were in certain fields/sections. Regarding public information services, the majority of 48% (OPD) use it through social media. Meanwhile, only 2 (OPD) use the website, this is a result of the lack of OPD that have a website or portal. While the media used to monitor the progress of public complaint services indicated that 38% (OPD) used email/telephone. The average value of public information services is 54.7% in the